Quartäre Formenwelt im Fussgebiet der Sierra Nevada Spaniens - Paschinger, Herbert (ERDKUNDE, 1961)
The Sierra Nevada is fringed in the north, west and southwest by wide piedmont surfaces which commence at 1,000-1,200 m. altitude and dip with a slope of 5-10°, and in two distinct steps, towards the foreland. They are erosion surfaces superimposed unconformably over late Tertiary strata and consist generally of limestone breccia, a few metres thick, with a very hard crust. Higher up this crust merges in places with slope breccia. Today the surfaces are dissected by valleys up to 150 m. deep. Owing to the absence of any direct link between the Pleistocene morainic deposits of the Sierra Nevada and the deposits making up the piedmont surfaces, the dating of the latter still remains only relative. According to one fossil find and other indications, the Alhambra conglomerate must be considered of Pluvial age. The piedmont surface with its two steps owes its origin to two periods of Pluvial sheet wash and subaerial erosion. Since solifluction during the cold (glacial) periods reached down to about 800 m. - at Vega near Granada to 650 m. -frost debris also played an important part in their formation. It is likely that there were three Pluvial periods in the Sierra Nevada region.